Case Report: Primary breast leiomyosarcoma in an 84-year-old male - Yang, Jie; Liu, Wei; An, Jie; Jiao, Cheng; Li, Zhi; Qi, Shuai; Hao, Chen; Zhang, Yao; Wang, Hui-Lin; Guo, Jun (Frontiers in Oncology, 2025)
Primary breast leiomyosarcoma is an extremely rare malignancy originating from mesenchymal tissue. Fewer than 10 male cases have been reported globally. This paper reports an 84-year-old male patient. This represents the oldest reported case in the current literature. A painless, slowly enlarging mass was present in his right breast. The mass had a 10-year history. This contrasts sharply with the typically rapidly progressive pattern documented in previous literature. Clinical examination revealed a mobile mass measuring 12 cm × 10 cm in the right breast. No lymphadenopathy was detected. Ultrasound showed a hypoechoic lesion classified as BI-RADS 4a. Magnetic resonance imaging demonstrated plateau-type enhancement. The patient underwent simple mastectomy. Axillary lymph node dissection was not performed. Postoperative pathology and immunohistochemistry confirmed the diagnosis of breast leiomyosarcoma. The patient declined adjuvant radiotherapy. Follow-up at 6 months postoperatively showed no local recurrence or metastasis. This case indicates several points to clinicians. Immunohistochemistry serves as the cornerstone for diagnosing spindle cell tumors of the breast. R0 surgical resection constitutes the core approach for achieving cure. Decisions regarding adjuvant therapy require full consideration of host age and tumor biological behavior. The senescent microenvironment in elderly patients may suppress aggressive tumor progression.